An integrative multi-omics analysis based on disulfidptosis-related prognostic signature and distinct subtypes of clear cell renal cell carcinoma - Zhang, Dong; Zhang, Xi; Liu, Zhanpeng; Han, Tian; Zhao, Kai; Xu, Xinchi; Zhang, Xu; Ren, Xiaohan; Qin, Chao (Frontiers in Oncology, 2023)
Background: The association between clear cell renal cell carcinoma (ccRCC) and disulfidoptosis remains to be thoroughly investigated. Methods: We conducted multiple bioinformatics analyses, including prognostic analysis and cluster analysis, using R software. Additionally, we utilized Quantitative Real-time PCR to measure RNA levels of RNA for specific genes. The proliferation of ccRCC was assessed through CCK8 and colony formation assays, while the invasion and migration of ccRCC cells were evaluated using the transwell assay. Results: In this study, utilizing data from multiple ccRCC cohorts, we identified molecules that contribute to disulfidoptosis. We conducted a comprehensive investigation into the prognostic and immunological roles of these molecules. Among the disulfidoptosis-related genes, LRPPRC, OXSM, GYS1, and SLC7A11 exhibited significant correlations with ccRCC patient prognosis. Based on our signature, patients in different groups displayed varying levels of immune infiltration and different mutation profiles. Furthermore, we classified patients were further divided into two clusters and multiple function pathways were identified multiple functional pathways that play important roles in the occurrence and development of ccRCC. Given its critical role in disulfidoptosis, we conducted further analysis was conducted on SLC7A11. Our results demonstrated that ccRCC cells with high expression of SLC7A11 exhibit a malignant phenotype. Conclusions: These findings enhance our understanding of the underlying function of disulfidoptosis-related genes in ccRCC.